Oryza Sativa L. Indica Ointment Effect on Histopathological Skin and Collagen Features in Ultraviolet B-Exposed Rattus novergicus - Minanti, Yuliana; Nasution, Sri Wahyuni; Dewani, Yunita; Delfian, Taufik (Poltekkes Kemenkes Palu, 2024)
Outdoorsy folks get UV radiation. Acute UVB decreases hyaluronic acid. Antioxidants can prevent photoaging by delaying, stopping, or eliminating oxidation-induced molecular damage. Black rice extract ointment (Oryza sativa l. indica) was tested on the histological features of skin and collagen in Wistar rats (Rattus norvegicus) subjected to ultraviolet B radiation. This study is lab-based. The research samples were Wistra strain white mice (Rattus norvegicus). Reaserch with treatment groups is Precondition variables (UVB rays), independent factors (10%, 20%, and 30% black rice extract ointment), and fixed variables (dermis collagen and histological picture of mice exposed to UVB rays) were the research variables. The research procedures included the accreditation of test animals, black rice extract, ointment, phytochemical screening, treatment, histopathological skin tissue preparations, and histopathological observation. All the data was examined with SPSS. The investigation revealed that 30% black rice extract ointment had the highest collagen density (mean and SD = 55,959 ± 2.5). All groups K-, K+, P1, P2, and P3 had significant data normality tests of 0.200 > 0.05. The homogeneity p-value is 0.06 > 0.05, and the sig (2-tailed) value is 0.000 < 0.05 in the t-test. The alkaloids, flavonoids, tannins, and steroids in black rice extract increase glutathione peroxidase levels in mice, which helps collagen density when exposed to UVB light at 125 mg/kg BW.